1977
DOI: 10.1038/hdy.1977.69
|View full text |Cite
|
Sign up to set email alerts
|

Matromorphy in Nicotiana rustica

Abstract: SUMMARYThe possibility of obtaining instant pure-breeding lines by matromorphic seed development in If. rustica has been investigated. Maternal parents homozygous for recessive marker genes and heterozygous for dominant marker genes were pollinated with different .Jficotiana species and with irradiated pollen of a X rust lea variety having a dominant marker. Poilinations with 65 species and with irradiated varietal pollen receiving doses ranging from 8 to 40 kr X-and gamma rays were performed on as many as 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…We have now achieved transformation of the egg in four distinct species of Nicotiana, and in addition Virk et al (1977) in Birmingham have independently shown a similar result for a further species of Nicotiana, N. rustica. The method is applicable to both self-compatible and self-incompatible female parents.…”
Section: Gametic Transformationsupporting
confidence: 52%
“…We have now achieved transformation of the egg in four distinct species of Nicotiana, and in addition Virk et al (1977) in Birmingham have independently shown a similar result for a further species of Nicotiana, N. rustica. The method is applicable to both self-compatible and self-incompatible female parents.…”
Section: Gametic Transformationsupporting
confidence: 52%
“…A modification of this technique involves the use of highly irradiated pollen not for producing true matromorphs but for the limited transfer of characters from one genotype to another. Evidence has been presented for the success of irradiated pollen technique in effecting the selective transfer of both qualitative and quantitative traits in Nicotiana (Virk et al, 1977;Pandey, 1978; Caligari et a!., 1981) and barley (Powell et a!., 1983). The experiments described in this paper report such an attempt in Indian mustard.…”
Section: Introductionmentioning
confidence: 99%
“…Despite reports of its widespread occurrence in this and other genera (e.g., Goodspeed, 1954;Eenink, 1974a, b) the attempts met with only limited success. When heavily irradiated pollen was used, many of the offspring, although not strictly matromorphic (since families derived from them segregated for one or more of the parental differences), did show a general resemblance to their mothers (Virk et a!., 1977). Subjecting the pollen of N. rustica to near-lethal doses of radiation therefore appeared not to produce true matromorphy but to offer the possibility of transferring parts of the DNA from one genotype to another (Mather, 1981).…”
Section: Introductionmentioning
confidence: 99%